2020
DOI: 10.4491/eer.2020.105
|View full text |Cite
|
Sign up to set email alerts
|

Fixed bed utilization for the isolation of xylene vapor: Kinetics and optimization using response surface methodology and artificial neural network

Abstract: This paper discusses the isolation of xylene vapor through adsorption using granular activated carbon as an adsorbent. The operating parameters investigated were bed height, inlet xylene concentration and flow rate, their influence on the percentage utilization of the adsorbent bed up to the breakthrough was found out. Mathematical modeling of experimental data was then performed by employing a response surface methodology (RSM) technique to obtain a set of optimum operating conditions to achieve maximum perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…= + 236.67 for 0.5% saturation (32) = 52.5 + 16.67 for 90% saturation (33) From the slope values, it was evident that the two lines were almost parallel to each other and the distance between them was found out to be 4.41 cm. This distance was referred as the height of exchange zone.…”
Section: Breakthrough Curve Modellingmentioning
confidence: 89%
See 1 more Smart Citation
“…= + 236.67 for 0.5% saturation (32) = 52.5 + 16.67 for 90% saturation (33) From the slope values, it was evident that the two lines were almost parallel to each other and the distance between them was found out to be 4.41 cm. This distance was referred as the height of exchange zone.…”
Section: Breakthrough Curve Modellingmentioning
confidence: 89%
“…Design of a full scale fixed bed adsorption columns requires collection of data obtained from the laboratory scale pilot column through the analysis of breakthrough curves at different flow rates, bed heights and initial As(III) ions concentration [33]. Dynamics of the fixed bed columns are expressed in terms of their kinetic models.…”
Section: Breakthrough Curve Modellingmentioning
confidence: 99%
“…12,13 adsorption is characterized based on the Thomas, bed depth service time, and Yoon−Nelson models, obtaining a high degree of fit between experimental data and model values. 14,15 Studies in the related literature have indicated that during the adsorption of VOC mixtures, competitive adsorption occurs, i.e., a phenomenon involving the displacement of molecules of one adsorbate from the adsorption bed by molecules of another adsorbate. 16−20 For binary VOC mixtures, the breakthrough curves can be divided into characteristic areas:…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of VOCs from the gas and liquid phases has been the focus of scientific research but often involves only one component. , For single-component experiments, fixed bed adsorption is characterized based on the Thomas, bed depth service time, and Yoon–Nelson models, obtaining a high degree of fit between experimental data and model values. , Studies in the related literature have indicated that during the adsorption of VOC mixtures, competitive adsorption occurs, i.e., a phenomenon involving the displacement of molecules of one adsorbate from the adsorption bed by molecules of another adsorbate. For binary VOC mixtures, the breakthrough curves can be divided into characteristic areas: (1) the outlet concentrations of both components are close to zero; (2) the mass transfer zone of the component with a lower adsorption affinity reaches the outlet of the adsorption column; (3) the outlet concentration of the less adsorbed component exceeds the value of its inlet concentration (displacement from the bed by the component with a higher adsorption affinity); (4) the mass transfer zone of the better-adsorbed component reaches the column outlet, and the outlet concentration of the component increases; and (5) the adsorption bed is completely saturated, and the outlet concentrations are close to the initial concentrations …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ANOVA provides researchers with insight into the statistical findings, which they can use to evaluate the models’ suitability (Singh & Kumar, 2020). This strategy has been applied to a wide range of research, engineering, and technology disciplines (Gupta & Kumar, 2020; Wang et al., 2011). Hence, the present work evaluates the use of reduced quantity of alum alongside LCSE as hybrid coagulant for the treatment of dye laden wastewater.…”
Section: Introductionmentioning
confidence: 99%